2015 IEEE 6th International Workshop on Computational Advances in Multi-Sensor Adaptive Processing (CAMSAP) 2015
DOI: 10.1109/camsap.2015.7383812
|View full text |Cite
|
Sign up to set email alerts
|

Resolving scaling ambiguities with the ℓ1/ℓ2 norm in a blind deconvolution problem with feedback

Abstract: Compared to more mundane blind deconvolution problems, blind deconvolution in seismic applications involves a feedback mechanism related to the free surface. The presence of this feedback mechanism gives us an unique opportunity to remove ambiguities that have plagued blind deconvolution for a long time. While beneficial, this feedback by itself is insufficient to remove the ambiguities even with`1 constraints. However, when paired with an`1/`2 constraint the feedback allows us to resolve the scaling ambiguity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Note that w(•) can not be explicitly determined from (27). By applying a proximal gradient method (PGM) [45], [46], [47] on the model (26), we obtain the following scheme…”
Section: Gradient-based Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that w(•) can not be explicitly determined from (27). By applying a proximal gradient method (PGM) [45], [46], [47] on the model (26), we obtain the following scheme…”
Section: Gradient-based Methodsmentioning
confidence: 99%
“…Since the gradient of the L 2 norm is ∇ x 2 = x x 2 , Lemma 2 implies that the gradient of Euclidean norm is Lipschitz-continuous in the domain {x | Ax = b}. The next lemma is about the Lipschitz property for the implicit function w(•) that satisfies (27).…”
Section: Convergence Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…However, in [11], Benichoux et al showed that use of the norm ℓ 1 suffers from scaling and shift ambiguities due to the nonlinear relation between the blurring kernel and the signal, as also discussed in [12,13]. Felix et al extended this result for the case of ℓ p , (p < 1)-norm in [14]. In particular, both of these reports showed that using the ℓ 1 /ℓ 2 function can overcome this difficulty.…”
Section: Introductionmentioning
confidence: 92%